PENDIDIKAN MULTIKULTURAL DAN NASIONALISME INDONESIA - Tukiran Tukiran (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2014)
AbstractIn this article the author promotes a conception of multicultural education and its role for the formation of Indonesian nationalism. Various references indicate that today there are some problems, mainly related to the development of narrow ethnic consciousness in some areas of the country. Not infrequently inter- ethnic relations have led to excessive sentiment in some areas so disrupt national unity built since this nation stands. This phenomenon encourages awareness to make an effort to develop nationalism among the people of In donesia. In this case, multicultural education can be adopted for the solution of the problem. Multicultural education appropriate to build Indonesian nationalism in the face of global challenges, because it has a core value in the local and global perspectives, namely: (a) piety towards God Almighty, (b) the responsibility of the unitary state, (c) an award, recognition, and acceptance of cultural diversity, (d) uphold the rule of law, and (e)appreciation of human dignity and human rights are universal. The goal of multicultural education is very importa nt for the integration of the nation because it is in line with Indonesian nationalism development efforts to address the challenges of time.